Citrus: Safe Handling Practices for Consumers - Amy Simonne; Mark Ritenour (EDIS)
Fresh citrus is rich in many nutrients and has not been traced to any cases of foodborne illness. However, fresh unpasteurized orange juice has been associated with several outbreaks of foodborne illnesses. This document describes steps you can take to reduce your risk of foodborne illness from fresh citrus and home made citrus juice. This publication is FCS8739, one of a series of the Department of Family, Youth and Community Sciences, Florida Cooperative Extension Service, IFAS, University of Florida. Publication: November 2002.